Pb(II) and Cu(II) Adsorption and Desorption Kinetics on Ferrihydrite with Different Morphologies. Issue 1 (25th January 2018) - Tian, Lei; Liang, Yuzhen; Lu, Yang; Peng, Lanfang; Wu, Pingxiao; Shi, Zhenqing
Abstract : Core Ideas: Gellike and dense ferrihydrite had different structures and Pb/Cu distributions. Ferrihydrite morphology and solution chemistry affected sorption and desorption kinetics. The kinetics model successfully described the stirred‐flow kinetic data of Pb and Cu. Different binding sites controlled adsorption and desorption kinetics differently. Understanding the effect of ferrihydrite morphology on the kinetic reactions of metals with ferrihydrite is essential for predicting the dynamic behavior of metals in soil. In this study, kinetics of Pb(II) and Cu(II) adsorption and desorption on two types of ferrihydrite, the freshly precipitated gellike ferrihydrite and freeze‐dried dense ferrihydrite representing two typical morphologies under extreme soil conditions, were studied. The high‐resolution transmission electron microscopy (TEM) images revealed that the gellike ferrihydrite loosely aggregated with open structure, while the dense ferrihydrite compactly aggregated with more consolidated and thicker structure. The energy dispersive spectroscopy (EDS), at the nanometer scale, showed that Pb(II) and Cu(II) distributed evenly on gellike ferrihydrite but localized on dense ferrihydrite after adsorption. The stirred‐flow kinetic experiments showed that higher pH and higher influent metal concentrations increased metal adsorption for both types of ferrihydrite. The dense ferrihydrite adsorbed slower and much less metals than gellike ferrihydrite because of less reactive sites. The desorption of heavy metals from ferrihydrite was affected by combined factors of the ferrihydrite morphology, adsorbed metal concentrations, pH, and metal re‐adsorption rates. The mechanic kinetics model based on the CD‐MUSIC model successfully described the adsorption and desorption kinetics of Pb(II) and Cu(II) on both gellike and dense ferrihydrite under various chemistry conditions. Our model provided quantitative tools for considering the effects of ferrihydrite morphology and heterogeneous binding sites under varying solution chemistry conditions when predicting the dynamic behavior of Pb(II) and Cu(II) in soil environment.